Arruamentos na proteção de Áreas de Preservação Permanentes (APP’s) urbanas na APA da Bacia Hidrográfica do Rio Machado – MG. - Ribeiro, Pedro Sousa Silva De Paula (2021)
The growth of cities can cause significant changes ins natural environments such as occupations in Permanent Preservation Areas (APP) referring to water courses. Located in the south of Minas Gerais, the Environmental Protection Area (APA) of the Machado River Basin, a state Conservation Unit that aims to protect water resources and riverside ecosystems, has three urban centers on its boundary, the cities of Fama, Machado and Deep Well. Considering the municipal autonomy in the environmental management of the urban perimeter, the legal alignment between the municipality and the state is a reality. This work aims to analyze, through satellite images, the interventions that took place in APA APP's between the years 2008 and 2020, justifying the respect for the consolidated use from that date onwards. It started from the hypothesis that the position of the streets may or may not favor the degradation of APP's in urban growth processes over time. This study makes use of hermeneutics referring to environmental legislation and a case study in which all sub-basins with influence on urban areas were selected as a sample area. Consultation by satellite images of the drainage network, followed by maps of points of interest, followed by complementary field reconnaissance and recording of photographs. For the methodological steps, free tools were used for data collection and processing, such as Google Earth Pro, CAR and Qgis. 2, 13 and 12 sub- basins were sampled in Fama, Machado and Poço Fundo respectively. It was verified occupations in APP's in all cities, being only Fama the one that did not present expansion of the urban fabric. The position of streets and public roads by limiting APP's with lots exerted a barrier to new occupations in the protective lanes, although the allocation of this infrastructure is not contemplated in any consulted rule. On the contrary, when the lots have APP's at their limit, anthropization in the protected area becomes more frequent. It was concluded that the spatial arrangement of urban infrastructure, through the position of streets and roads limiting buildable areas, can contribute to the conservation of natural areas as cities grow. Thus, planning the expansion of cities can support the APA management plan, with a proposal for environmental zoning that need to be aligned with the respective master plans of the municipalities.